The Importance of Chess in Enhancing Students' Creativity in the Educational Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the importance of chess in enhancing students' creativity in the educational process. Playing chess develops problem-solving skills, strategic thinking, and unconventional approaches. Studies show that chess lessons not only foster creative thinking but also strengthen students' logical and critical thinking abilities. Incorporating chess into school curricula serves to enhance both intellectual potential and creative abilities. Future research is encouraged to further investigate the effects of chess on different age groups and educational levels to expand knowledge in this field.